2011
DOI: 10.1088/0957-0233/22/10/104020
|View full text |Cite
|
Sign up to set email alerts
|

Phase fraction distribution measurement of oil–water flow using a capacitance wire-mesh sensor

Abstract: In this paper, a novel wire-mesh sensor based on permittivity (capacitance) measurements is applied to generate images of the phase fraction distribution and investigate the flow of viscous oil and water in a horizontal pipe. Phase fraction values were calculated from the raw data delivered by the wire-mesh sensor using different mixture permittivity models. Furthermore, these data were validated against quick-closing valve measurements. Investigated flow patterns were dispersion of oil in water (Do/w) and dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(17 citation statements)
references
References 22 publications
0
16
0
1
Order By: Relevance
“…In order to deal with the above-mentioned indetermination and flow regime dependence, many researchers have applied mixture models based on different assumptions, for instance the parallel model [41], the expanded Maxwell-Model for three phase [27] and more recently the Maxwell model for air-water flows [42].…”
Section: B Continuous Phase Inversionmentioning
confidence: 99%
“…In order to deal with the above-mentioned indetermination and flow regime dependence, many researchers have applied mixture models based on different assumptions, for instance the parallel model [41], the expanded Maxwell-Model for three phase [27] and more recently the Maxwell model for air-water flows [42].…”
Section: B Continuous Phase Inversionmentioning
confidence: 99%
“…The WMS data yields the instantaneous local mixture permittivity values, e m (i, j, k), measured within a volume of 2.00 mm (distance between the transmitting and receiving wires of WMS) Â 4.75 mm (WMS grid resolution) Â 4.75 mm (WMS grid resolution) using the serial model [22] in conjunction with the gas and liquid calibration data, and is given by…”
Section: Spatially Averaged Liquid Holdupmentioning
confidence: 99%
“…It is also clear from the presented literature that there is still need for further understanding on the flow topology for larger pipe diameters, which will improve the closure relationships in the two-fluid models. In recent years, high-speed cameras and Wire Mesh sensors are used for the flow diagnostics tools in multiphase research, and yield detailed quantitative and qualitative information on the flow topology [20][21][22]. Therefore, this study focuses on the features of the interface topology and the wave dynamics in oil-gas, two-phase stratified-wavy flow at a large pipe diameter by facilitating the Wire Mesh sensors and a hi-speed camera.…”
Section: Introductionmentioning
confidence: 99%
“…The electrode of the intrusive capacitive sensor is in contact with the fluid directly, resulting in the higher sensitivity and faster response speed. Silva et al [8] measured the phase distribution on the pipe cross-section using a wire-mesh capacitive sensor. Liu et al [9] investigated the performance of a coaxial capacitance sensor in the water-hold-up measurement, and found that the region near the inner electrode had higher sensitivity.…”
Section: Introductionmentioning
confidence: 99%